Harmony With Enviroment Secret of The Succes Story? - Husain Haikal (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2007)
This autobiography is a part of history, as many parts of its content reveal dynamic aspects of life in West Sumatera. Its author provides the importance of living in harmony with the environment.